2022
DOI: 10.1088/1361-6463/ac43dd
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in THz detectors based on semiconductor structures with quantum confinement: a review

Abstract: Beginning from the 1990s, an ever-lasting interest in the THz spectroscopy and THz instruments has produced wide progress in the development of high-speed THz detectors. The constantly growing requirements aimed at the increase of spectral resolution, sensitivity, and acquisition rate of THz detectors have attracted much attention in this field till nowadays. In the present review, we summarize the most recent advances in the THz photodetectors based on semiconductor structures with quantum confinement of an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 143 publications
1
5
0
2
Order By: Relevance
“…DOI: 10.21883/PJTF.2022. 23.53944.19332 Спектрометры и системы построения изображений на основе фотопроводящих антенн (ФПА) для преобразования энергии ультракоротких импульсов лазерной накачки в электромагнитные колебания терагерцевого (THz) диапазона частот активно применяются для решения широкого спектра фундаментальных и прикладных задач [1][2][3]. Использование ФПА в оптической схеме спектрометра с временн ым разрешением (time-domain spectroscopy, TDS) дает возможность одновременно получать информацию об амплитуде и фазе принимаемого THz-излучения в широкой полосе частот, что повышает эффективность алгоритмов восстановления изображений в задачах томографии и неразрушающего контроля [4].…”
Section: поступило в редакцию 3 августа 2022 г в окончательной редакц...unclassified
“…DOI: 10.21883/PJTF.2022. 23.53944.19332 Спектрометры и системы построения изображений на основе фотопроводящих антенн (ФПА) для преобразования энергии ультракоротких импульсов лазерной накачки в электромагнитные колебания терагерцевого (THz) диапазона частот активно применяются для решения широкого спектра фундаментальных и прикладных задач [1][2][3]. Использование ФПА в оптической схеме спектрометра с временн ым разрешением (time-domain spectroscopy, TDS) дает возможность одновременно получать информацию об амплитуде и фазе принимаемого THz-излучения в широкой полосе частот, что повышает эффективность алгоритмов восстановления изображений в задачах томографии и неразрушающего контроля [4].…”
Section: поступило в редакцию 3 августа 2022 г в окончательной редакц...unclassified
“…Research efforts in the THz detection technology have resulted in thermal, optical, and semiconductor-based detection processes. [1][2][3][4][5] Recent studies have shown the potential of optomechanical detection systems. [6][7][8] Golay cells are widely used detectors to be applied not only in the THz, but a considerably wide spectral range can be covered from ultraviolet (UV) to millimeter wavelengths.…”
Section: Introductionmentioning
confidence: 99%
“…DOI: 10.21883/PJTF.2023.02. 54279.19395 Значительное развитие методов генерации терагерцевых (THz) волн открыло широкие возможности для применения данного излучения во многих областях науки [1,2]. Существенный прогресс наблюдается в генерации частот от 100 GHz до 1 THz с использованием умножителей, диодов Ганна [3] и транзисторов с высокой подвижностью электронов [4].…”
unclassified